METABOLOMIC TECHNIQUE IN GREEN TEA RESEARCH: A REVIEW - Kurnianto, Muhammad Alfid; Rini, Dina Mustika (UPN Veteran Jatim, 2024)
Tea, consumed by two-thirds of the global population, had a production of 5.68 million tons in 2017. The cultivation and processing of tea are crucial variables that have a substantial impact on the final product. As a result, many types of tea, such as black, oolong, and green, are produced, each with its own unique flavors and health advantages. Metabolomic techniques, which employ advanced analytical methods, are employed to characterize chemical composition of tea, thereby enabling the assessment of its quality, origin, and bioactivity. This review focused on the application of these techniques to the green tea research. Analytical methods such as UPLC-MS and 1H NMR, when employed in conjunction with multivariate analysis, have proven effective in correlating green tea quality with its chemical constituents, identifying key metabolites such as EGCG, ECG, and caffeine. These metabolomic techniques permit rapid and accurate assessments, enabling the differentiation between high- and low-quality green tea and enhancing the comprehension of its chemical composition and sensory attributes. In addition, a metabolomic approach was employed, utilizing HPLC-TOF-MS, to differentiate between various types of green tea based on their bioactivities. These methods have the capacity to reveal significant variations in metabolite profiles and bioactivities. The application of multivariate analysis enabled the identification of specific bioactive cultivars, thereby demonstrating the efficacy of the technique in evaluating the health-promoting effects of different tea samples. Thus, metabolomic methods represent an optimal approach for a comprehensive and expeditious investigation of the research related to green tea.